Jordan : Staff Report for the 2014 Article IV Consultation, Third and Fourth Reviews Under the Stand-By Arrangement, Request for Waivers of Nonobservance of Performance Criterion and Applicability of Performance Criteria. - International Monetary Fund. Middle East and Central Asia Dept. (Washington, D.C. : International Monetary Fund, 2014)
This paper focuses on Jordan's 2014 Article IV Consultation, Third and Fourth Reviews Under the Stand-By Arrangement (SBA), Request for Waivers of Nonobservance of Performance Criterion (PC) and Applicability of PCs. The program is broadly on track and, looking forward, will focus on deep tax reform. All end-2013 targets were met. The central government is expected to meet its end-March 2014 target, but the combined public sector deficit will be missed because of temporary shortfalls in gas delivery from Egypt. International reserves have continued to over-perform through March. The IMF staff supports the completion of the third and fourth reviews.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet